2015
DOI: 10.1016/j.pmrj.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Compression After Dry Needling of a Latent Myofascial Trigger Point Reduces Postneedling Soreness Intensity and Duration

Abstract: IC can potentially be added immediately after dry needling of myofascial trigger point in the upper trapezius muscle because it has the effect of reducing postneedling soreness intensity and duration. The combination of dry needling and IC seems to improve CROM in homolateral and contralateral cervical rotation movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
7
25
2
1
Order By: Relevance
“…This is the first study investigating the effects of low‐load exercise as a postneedling intervention in active TrPs. Previous studies investigating post‐dry needling interventions were conducted on asymptomatic subjects exhibiting latent muscle TrPs [20,21]. Similar to previous studies, postneedling soreness was present in 100% of the individuals who received TrP‐DN in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is the first study investigating the effects of low‐load exercise as a postneedling intervention in active TrPs. Previous studies investigating post‐dry needling interventions were conducted on asymptomatic subjects exhibiting latent muscle TrPs [20,21]. Similar to previous studies, postneedling soreness was present in 100% of the individuals who received TrP‐DN in our study.…”
Section: Discussionsupporting
confidence: 84%
“…There are few studies that have investigated therapeutic strategies to decrease postneedling‐induced pain. Two recent studies demonstrated that the application of ethyl chloride spray and stretching [20] and ischemic compression [21] after TrP‐DN exhibited short‐term effects (between 6 and 24 hours) for reducing postneedling soreness on latent TrPs in the upper trapezius. Although promising, these studies included asymptomatic subjects with latent TrPs, which does not represent clinical practice, and also applied passive modalities for reducing postneedling soreness.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding latent MTrPs, recent studies have shown that the application of ‘spray and stretch’ 14 or ischemic compression 15 after DN immediately decreased post-needling soreness compared to subjects who were only treated by DN. The use of DN plus PENS may have clinical relevance for professionals using DN in the treatment of MTrPs, since high post-needling soreness values are associated with patient dissatisfaction and reduced treatment adherence 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ischemic compression 15 , ‘spray and stretch’ 14 , and ultrasound 12 have been applied with positive effects, reducing both myofascial pain 16 and post-needling soreness 12 , 14 , 15 . According to recent studies, TENS operates via multiple pathways to reduce pain through various physiological mechanisms 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Como se estableció en la metodología, el presente estudio utilizó una escala de valoración verbal (EVA). En este estudio no se utilizó la escala analógica visual para valorar la eficacia de la intervención, sino para comprobar el dolor muscular generado por la misma, tal y como se ha empleado en otras investigaciones (346).…”
Section: Escala Analógica Visualunclassified